Efektivitas Pemanfaatan Media Pembelajaran di SMK Tritech Informatika Medan - Annisa Hananiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the effectiveness of the use of learning media starting from the use of effective learning media, supporting and inhibiting factors in the use of learning media, and the efforts made by schools to increase the effectiveness of the use of learning media at Tritech Informatics Vocational School, Medan. There are some teachers who still lack the ability to use school facilities to develop learning media. Teachers are not effective in utilizing existing learning media, making students less motivated to learn and not effective in designing interesting learning media. Apart from that, the audiovisual learning media that has been provided by the school in the podcast room is very rarely used or used and there are still some teachers who are not effective in using and choosing learning media. This research uses a type of qualitative descriptive research, namely by using a detailed approach to research objects sourced from primary and secondary data. In this study, the research subjects were school principals, teachers and students. The data collection technique used is first observation, then interviews and finally documentation. The instrument in this research uses interviews in the form of guidelines consisting of several questions. The data analysis technique in this research uses source triangulation, technique triangulation, and time triangulation. Based on the results of the research and discussion, it can be concluded that the effectiveness of using learning media is going well. Effective use of learning media has been implemented in the procedures for procuring learning media, maintaining learning media and using various learning media. Supporting factors are the completeness of learning media and designing learning media, inhibiting factors are media that depend on electricity which will become an obstacle if the lights go out. Efforts to effectively use learning media at Tritech Informatics Vocational School in Medan are carried out by paying attention to choosing the right use of learning media and effective and efficient management of learning media.